EFEKTIVITAS SENAM HAMIL TERHADAP NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI DESA SIKEBAU JAYA ROKAN IV KOTO - handayani, eka yuli; Marini, Susi; Wahyuny, Romy; Junita, Elvira; Yanti, Nina Surya Fitri (AHM Center, 2025)
Pregnancy brings so many changes to a woman's body, women experience various kinds of discomfort during pregnancy, one of the discomforts that often arises is back pain. Management of low back pain during pregnancy is very necessary to reduce this discomfort, including pharmacological therapy and non-pharmacological therapy by doing pregnancy exercises. This study aims to determine the effectiveness of pregnancy exercise to reduce back pain in third trimester pregnant women in Sikebau Jaya Village, Rokan IV Koto. This research method is quantitative analytic with the research design used is pre-experimental with one group pre-test and post-test design. Data collection used a Sphygmomanometer, while data analysis used the T-Dependent test. The sample in this study was 14 third trimester pregnant women. The results of the research from the analysis of data on the average difference in back pain before and after doing pregnancy exercise is 1.8 with a standard deviation of 0.36. The conclusion is that there is an effect of pregnancy exercise on reducing the intensity of back pain in third trimester pregnant women in Sikebau Jaya Village, Rokan IV Koto District, Rokan Hulu Regency with (p value = 0.00). Suggestions to the village are that it is hoped that the results of this research can be a source of information for the village of Sikebau Jaya that doing pregnancy exercise to reduce back pain in third trimester pregnant women and conduct class discussions with pregnant classes